Staphylococcus aureus Masking Tuberculous Joint Infection - Mohammed A. Shaikhomer, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Skeletal tuberculosis accounts for around 10 percent of cases of extrapulmonary tuberculosis. Hip and knee involvement are the most commonly affected sites after spine. Clinical manifestations include swelling, pain, and loss of joint function that progress over weeks to months. In the setting of tuberculous arthritis, local soft tissue swelling, osteopenia, and bone destruction (with relative preservation of cartilage space) occur early in the disease. Subsequent findings include structural collapse, sclerotic changes, and soft tissue calcification. Delay in diagnosing tuberculous arthritis can lead to functional disability and poor outcome. Superimposed infection with another organism occurs very rarely and can lead to delay in diagnosing the condition. We present a case of tuberculous knee arthritis that was superimposed with Staphylococcus aureus infection. The low index of suspicion at the initial presentation together with the superimposed infection led to a delayed diagnosis. Our patient’s risk factor was immigration from a country endemic with tuberculosis. The case was diagnosed 32 months from initial presentation. In the presence of clinical and epidemiological risk for tuberculous arthritis, requesting the appropriate tests is crucial to avoid any diagnostic delay.